Pengaruh Kepuasan Kerja Dan Motivasi Kerja Terhadap Kinerja Dengan Organizational Citizenship Behavior (OCB) Sebagai Variabel Mediasi Pada LPP Rri Padang - Jolio Figo; Maivalinda (GLOBAL SCIENTS PUBLISHER, 2025)
Organizational Citizenship Behavior (OCB) can simply be described as individual behavior rooted in the willingness to contribute beyond one’s core role or responsibilities, whether consciously or unconsciously, directed or undirected, to provide benefits and advantages to the company. The purpose of this study is to determine the effect of Job Satisfaction and Work Motivation on Performance through Organizational Citizenship Behavior (OCB). The population in this study consists of all employees, with a total of 93 respondents. Data collection was conducted by distributing questionnaires directly to the respondents. The purposive sampling method was used to select the respondents. The implication of the conclusion above is that OCB cannot mediate the relationship between job satisfaction and performance, nor between work motivation and performance. This is because the influence of job satisfaction on performance and work motivation on performance does not require OCB as a mediating variable, as their influence is direct on performance without the need for OCB mediation.